Dualisme Sistem Pendidikan di Indonesia (Studi Kasus MAN 2 Kudus dengan Madrasah Aliyah Swasta) - Wif Da Untsa (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
Education can not apart from the education system itself. The education system implemented in educational institutions has a big role in determining student output. Educational institutions at the top level, for example at the high school level which incidentally under the Ministry of Education and Culture certainly have different goals from education at the level of MAN under the auspices of the Ministry of Religion. Judging from the output objectives to be achieved only conflict between one another, plus the compilation of the two education systems put together then what happens is the output of the educational institution will be half measures, so that the goals mentioned earlier can be used in accordance with what has been is expected. The writing of this article discusses the challenges of dualism in the education system in Indonesia by using literature and comparative studies, as well as discussing the implications arising from this dualism, and being able to provide contributive solutions in the arena of Indonesia's education world.